2016
DOI: 10.1590/0103-9016-2015-0084
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the resistance of common bean to white mold through recurrent selection

Abstract: White mold, caused by Sclerotinea sclerotiorum (Lib.) de Bary is one of the most important diseases of the common bean (Phaseolus vulgaris L.) worldwide. Physiological resistance and traits related to disease avoidance such as architecture contribute to field resistance. The aim of this study was to verify the efficiency of recurrent selection in physiological resistance to white mold, "Carioca" grain type and upright habit in common bean. Thirteen common bean lines with partial resistance to white mold were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 24 publications
(38 reference statements)
5
35
0
Order By: Relevance
“…Although the lines derived from recurrent selection (84/6 and 50/5) exhibit good resistance to white mold by the straw test method as observed in this study and by Leite et al (2016), PvPGIP expression levels were still well below those demonstrated by Cornell 605, suggesting that the incorporation of lines with high expression levels of these genes in breeding programs can further improve the resistance levels of lines. Moreover, these genes were only expressed during the first days after inoculation with white mold, and from the fifth day after inoculation, all of the genes exhibited similar relative expression levels.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Although the lines derived from recurrent selection (84/6 and 50/5) exhibit good resistance to white mold by the straw test method as observed in this study and by Leite et al (2016), PvPGIP expression levels were still well below those demonstrated by Cornell 605, suggesting that the incorporation of lines with high expression levels of these genes in breeding programs can further improve the resistance levels of lines. Moreover, these genes were only expressed during the first days after inoculation with white mold, and from the fifth day after inoculation, all of the genes exhibited similar relative expression levels.…”
Section: Discussionmentioning
confidence: 46%
“…Four bean lines were used, including two resistant lines derived from a recurrent selection for white mold with a Carioca grain type of Mesoamerican origin and adapted to growing conditions in southeastern Brazil (Leite et al, 2016), one non-adapted source of resistance (Cornell 605;Griffiths, 2009), and one susceptible to white mold as a control (Corujinha; Silva et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is known that genetic or physiological resistance currently observed in Brazilian breeding programs is insufficient to ensure stable crop yields in regions with a climate favorable to the pathogen and under high pressure of the disease (Carneiro et al 2011, Gonçalves and Santos 2010, Lehner et al 2015. Although simple inheritance of resistance has been reported for WM in dry beans (Genchev and Kiryakov 2002, Schwartz et al 2006, Antonio et al 2008, partial or quantitative resistance with additive effects is predominant (Carneiro et al 2011, Schwartz and Singh 2013, Leite et al 2016, Vasconcellos et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Sources of partial resistance to WM have been identified in P. vulgaris (Schwartz and Singh 2013, Lehner et al 2015, Vasconcellos et al 2017. In general, they are not adapted to Brazilian environmental conditions; however, they can be used as parents in breeding programs to obtain segregating populations from which to extract WM resistant elite lines (Antônio et al 2008, Leite et al 2016. A strategy for selecting parents in plant breeding programs based on progeny information is estimation of combining abilities by diallel crosses.…”
Section: Introductionmentioning
confidence: 99%